Visual field (Octopus 1-2-3) in normal subjects divided into homogeneous age-groups - Calixto,Nassim (2006)
PURPOSE: To determine the values in decibels of retinal sensitivity within the central 26 degrees of the visual field of normal subjects divided into homogenous age groups using the Octopus 1-2-3; to compare the values of retinal sensitivity we have found with those considered normal in the statistical package obtained by a multicenter study performed in 1994 with Octopus 201. METHODS: 181 subjects divided into 6 homogeneous age groups (10 to 19 yr; 20 to 29 yr; 30 to 39 yr; 40 to 49 yr; 50 to 59 yr and 60 year-old or older) were evaluated. Data on visual sensitivity and age, average sensitivity of central and paracentral regions and eccentricity were calculated. RESULTS: The average visual sensitivity of all groups was 26.77 ± 1.74 dB. Correlation between visual sensitivity and age evaluated by linear regression was 28.4 - 0.040 x (age) for the whole sample and 28.7 - 0.050 x (age) for subjects aged 20 or more. Sensitivity reduction by eccentricity was -0.30 dB/degree for the whole sample and for subjects aged 20 or more. CONCLUSIONS: Correlation between retinal sensitivity values and age based on the autoperimeter Octopus 201 (average sensitivity of 31.2 - 0.064 x age) is different from that found in this study: average sensitivity of 28.4 - 0.040 x (age) for the whole sample; 28.7 - 0.050 x (age) for subjects aged 20 or more. Values obtained with the Octopus 1-2-3 autoperimeter cannot be compared with those by other Octopus models (101, 201 and 500) due to their distinct features.